A systematic review on the economic burden of interstitial lung disease and the cost-effectiveness of current therapies - Alyson W. Wong; John Koo; Christopher J. Ryerson; Mohsen Sadatsafavi; Wenjia Chen (BMC Pulmonary Medicine, 2022)
Abstract Background The economic burden of interstitial lung disease (ILD) is unknown, limiting informed resource allocation and planning. We sought to conduct the first systematic review on the direct, indirect, and overall costs associated with ILD and to evaluate the cost-effectiveness of current therapies globally. Methods We conducted systematic reviews of ILD disease cost studies and cost-effectiveness analyses (CEAs) using MEDLINE, Embase, and Web of Science databases between 2000 and 2020. We compared ILD costs between countries according to the share of costs towards each country’s respective gross domestic product (GDP) per capita. Costs are reported in 2020 USD. Results We identified 25 disease cost studies and 7 CEAs. The direct medical costs ranged between $1824 and $116,927 annually per patient (median $32,834; 14–180% of GDP per capita in Western countries). The leading drivers of direct costs were inpatient (55%), outpatient (22%), and medication costs (18%), based on pooled estimates. Annual indirect costs ranged from $7149 to $10,902 per employed patient (median $9607; 12–23% of GDP per capita). Among the 7 CEAs, only 1 study (14%) showed an ILD therapy (ambulatory oxygen) was cost-effective compared to best supportive care. Conclusion The direct and indirect costs associated with ILD are consistently high in all countries with available data, with cost-effectiveness profiles of new therapies generally undesirable. Globally, the median total direct cost for ILD equates to 51% of a country’s GDP per capita and has been increasing over time.